Growth and volatiles in the micropropagation of Santa Maria herb - Carvalho, Alexandre; Bertolucci, Suzan Kelly; Silva, Sâmia; Pinto, José Eduardo (Revista Ciência Agronômica, 2018)
The aims of this study were to establish micropropagation for Chenopodium ambrosioides L. and analysis of volatile constituents in vitro as a function of different salt concentrations of MS medium and sucrose. The apical buds were established on MS medium added with 3% sucrose. The vegetative growth of nodal segments was tested in different salt concentrations of MS basic medium (0.25, 0.50, 1.00, 1.50, and 2.00) and of sucrose (5, 10, 20, 30, and 40 g L-1). Nodal and apical segments were tested in vertical and horizontal orientations. Different volumes of culture medium (20; 35, 50, 65, and 80 mL) were examined in the growth of nodal segments. Plants were acclimatized in three different substrates. The apical segments collected from matrices plants were successful when established in MS medium. A multiplication rate of 8.5 was obtained with nodal and apical segments without using growth regulator. MS medium with its salt concentration reduced by half (0.50 MS) and sucrose at the concentration of 30 g L-1 provided better in vitro growth of nodal segments. Four major volatile compounds (α-terpinene, p-cymene, Z-ascaridole, and E-ascaridole) varied at different salt concentrations and only α-terpinene showed difference for sucrose concentrations. Apical segments in vertical orientation and nodal segments in horizontal with 50 mL of culture medium showed better responses for the in vitro cultivation of C. ambrosioides L.